PELATIHAN DIGITALISASI FARMASI IKATAN APOTEKER INDONESIA (IAI) PC KOTA SALATIGA - Prastiyo, Angga; Hati, Anita Kumala (Sekolah Tinggi Ilmu Ekonomi AMA, 2024)
Pharmacists/pharmacy services need to improve their professionalism in order to keep up with the rapid development of technology. Digitalization applied in the pharmaceutical world needs to be accompanied by a “human touch”. One of the efforts that can be made by IAI PC Salatiga City members is to understand and innovate in the use of health service technology. The solution to the problems that occur is to conduct training and understanding of digital transformation which has now become a necessity for the industrial world, especially the pharmaceutical sector. One of the factors that accelerates the process, so that many business operations today can be shortened and more efficient due to digitalization. One of the important characteristics of the pharmacist profession is adaptability. There was a significant increase in participants' knowledge before and after the training, this was based on the increasing enthusiasm of the participants in asking questions and actively participating in this activity. The IAI Salatiga City pharmacy digitalization training is expected to create enthusiasm to be able to continue to develop the knowledge and insights of participants, especially members of the Indonesian Pharmacists Association (IAI) PC Salatiga City to improve services to the community.Suggestions for IAI PC Salatiga City members, frequent training activities for digitalization of pharmaceutical services and preparing members who understand digitalization to be able to achieve health development targets, especially the change from the analog to the digital era.